The role of teachers and parents to improve children’s motivational learning in pandemic situation - Sri Astuti; Diki Rukmana; Puri Pramudiani; Zulherman Zulherman (Institute of Advanced Engineering and Science, 2022)
This study analyzed the teachers' and parents' synergy in motivating children to take online learning at home during the COVID-19 pandemic in Indonesia. The research instrument consisted of 13 survey questions distributed via Google Form and succeeded in capturing 139 samples of parents of preschool and elementary school students spread across 17 provinces in Indonesia. Factor analysis and structural equation modeling (SEM) were conducted to analyze the instrument's validity and test hypotheses. The factor analysis results showed that the 13 instruments used showed an excellent correlation to confirm each variable's structure. The SEM analysis results showed that in the online learning system applied to preschool and elementary school children, parents play a significant role in the children's motivation to take online learning at home. Parents were also a positive and significant mediator variable in the teacher's role in increasing children's learning motivation. These results indicated that parents' and teachers' motivating children to carry out online learning at home during the COVID-19 pandemic in Indonesia must be established and continuously improved. The contribution was a reference for those who intend to develop an appropriate online learning system framework for preschool and elementary school children.